Co-offending as social exchange. Explaining characteristics of co-offending - Weerman, Frank M. (The British journal of criminology, 2003)
Studies in the past have already revealed some interesting characteristics of co-offending, but relatively little attention has been paid to explaining them. This paper is focused on the explanation of these characteristics. A comprehensive theory is proposed, based on the idea that co-offending may be viewed as an event in which material and immaterial goods are exchanged. The basic concepts of such a social exchange theory are formulated in this article, and a causal model based on this theory is deduced. The paper also shows how the proposed theory may explain the well-known characteristics of co-offending